2022
DOI: 10.1073/pnas.2202118119
|View full text |Cite
|
Sign up to set email alerts
|

Logic-enabled textiles

Abstract: Textiles hold great promise as a soft yet durable material for building comfortable robotic wearables and assistive devices at low cost. Nevertheless, the development of smart wearables composed entirely of textiles has been hindered by the lack of a viable sheet-based logic architecture that can be implemented using conventional fabric materials and textile manufacturing processes. Here, we develop a fully textile platform for embedding pneumatic digital logic in wearable devices. Our logic-enabled textiles s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 40 publications
(68 reference statements)
0
28
0
Order By: Relevance
“…For example, a single output temperature from a thermal circuit consisting of thermal OR gates could be used to detect whether any of the input temperatures ( , ,…., ) is above the switching temperature, as illustrated in Supplementary Figure 4 for . Like mechanical 68 , fluidic 69 , and textile 70 logic elements, thermal logic devices could potentially be applied for computation and sensing without requiring electrical power consumption, if a naturally occurring thermal gradient exists to establish and . Although nanoscale thermal–mechanical logic elements leveraging thermal expansion and gap-size-dependent thermal radiation have been demonstrated 71 , macroscopic thermal logic gates have not been reported.…”
Section: Resultsmentioning
confidence: 99%
“…For example, a single output temperature from a thermal circuit consisting of thermal OR gates could be used to detect whether any of the input temperatures ( , ,…., ) is above the switching temperature, as illustrated in Supplementary Figure 4 for . Like mechanical 68 , fluidic 69 , and textile 70 logic elements, thermal logic devices could potentially be applied for computation and sensing without requiring electrical power consumption, if a naturally occurring thermal gradient exists to establish and . Although nanoscale thermal–mechanical logic elements leveraging thermal expansion and gap-size-dependent thermal radiation have been demonstrated 71 , macroscopic thermal logic gates have not been reported.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, reducing the cost of SCT devices through the aforementioned fabrication approach stemming from soft robotics is particularly important because people of low socioeconomic status have more risk factors for cardiovascular diseases, and this low-cost device may provide more accessible treatment for those who need it. It has also been shown that devices of similar textile structures and materials to our device are machine washable and remain functional after 20,000 cycles of actuation, which is equivalent to 50,000 min of SCT for our device, making our device ideal for wearable purposes (Rajappan et al, 2022). Furthermore, the files used to create all parts of the device have been provided in the Supplementary Material to allow open-access fabrication.…”
Section: Discussionmentioning
confidence: 96%
“…For example, sewing the straps of the device into (or underneath) a pant leg would enable the device to be wearable like conventional garments yet still provide SCT in an inconspicuous and comfortable manner. The implementation of textile-based energy harvesting or logic control could enable the device to be made solely from textile materials, ensuring an entirely soft (and washable) device ( Rajappan et al, 2022 ; Shveda et al, 2022 ). The system could also be further developed to deliver SCT more precisely in an automatic manner by using closed-loop control ( Payne et al, 2018 ; Sanchez et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations